PERAN DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI KEPULAUAN BANGKA BELITUNG DALAM PENGAWASAN TERHADAP PEMBERIAN IZIN USAHA PERKEBUNAN YANG DILAKUKAN OLEH PEMERINTAH DAERAH PROVINSI KEPULAUAN BANGKA BELITUNG - Sandra Primadi (Fakultas Hukum Universitas Bangka Belitung, 2016)
A paradigm friction performanc e in the Parliament, and especially in terms of oversight has been pushed to the prioritize for interests and needs of the peoples. And then function of Parliament is a demanding to the implementation of functions in accordance with the expectations of the nation and society. And it has been arrenged in the Constitution number 17 of 2014 about MPR, DPR, DPD and DPRD, in this case the Parliament has already authority which is a form of representation of the people in area. That is problem to raised on my eassy is a about role. And then from the results obtained is a declare that is role and performance of Parliament Province of Bangka Belitung Islands must perspective and be a mandate to take tasks that have been given from the people, and under the supervision performance of local government the represents of aspirations and must or should be a pro-people. And that is must to do a government can functionate like a effectively and efficiently. And that is factors are a barrier of Parliament Province of Bangka Belitung Islands is a external factors that is come from outside of Parliament itself. And that conclusion in the supervision must be accordance with the aspirartions of the people and from the oustide Parliament Province of Bangka Belitung Islands.